Modelling and loss analysis of meso-structured perovskite solar cells - Xue, Hansong (2017)
A mathematical model for meso-structured perovskite solar cells is derived and calibrated towards measured intensity dependent current-voltage characteristics. This steady-state device model describes the transport of free carriers, carrier recombination and optical generation. The optical part considers internal transmission, reflection, and absorption of light, using a transfer matrix approach. The carrier recombination in the form of radiative, Auger and Shockley-Read-Hall mechanisms is accounted for inside the perovskite capping layer, as well as interfacial recombination between the perovskite and electron/hole-transporting layers. After calibration by best-fitting the unknown parameters towards intensity dependent current-voltage measurements of an in-house fabricated meso-structured perovskite solar cell, we identify the dominant recombination mechanisms and their locations inside the cell. A subsequent loss analysis indicates that, in our fabricated solar cell, the interfacial recombination between the perovskite/mesoporous titanium dioxide within the mesoporous absorber layer constitutes the main loss channel. This interfacial recombination accounts for up to 46% of all recombination losses at maximum power, thereby exceeding the recombination inside the perovskite capping layer with 31% loss. Furthermore, the thickness of the perovskite capping layer and the mesoporous layer is varied by means of simulation between 50 and 500 nm, in order to predict the optimum device geometry for the calibrated recombination parameters.